2016
DOI: 10.1111/ecc.12516
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for cancer-related fatigue: a scoping review

Abstract: Interventions for cancer-related fatigue: a scoping review Cancer-related fatigue (CRF) is common and can be distressing for some survivors. There is increasing interest in measuring levels of CRF, highlighting its impact on quality of life. This review describes the nature and scope of evidence relating to interventions for CRF. Scoping review methodology was used to identify studies, extract data, collate and summarise results. Data were collated according to cancer tumour streams, stage of illness and the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 86 publications
2
48
0
3
Order By: Relevance
“…Importantly, gCl is the electrical parameter sustained by the voltage‐gated chloride channel CLC‐1, which in turn is negatively regulated by the Ca 2+ ‐dependent protein kinase C (PKC) . As it has been proposed for several conditions of muscle wasting, the alteration of sarcolemma excitability may contribute to the mechanisms responsible for muscle tiredness and fatigue observed in patients undergoing chemotherapy, further corroborating the hypothesis that calcium dysfunction could be strictly related to cachectic muscle impairment.…”
Section: Discussionmentioning
confidence: 57%
“…Importantly, gCl is the electrical parameter sustained by the voltage‐gated chloride channel CLC‐1, which in turn is negatively regulated by the Ca 2+ ‐dependent protein kinase C (PKC) . As it has been proposed for several conditions of muscle wasting, the alteration of sarcolemma excitability may contribute to the mechanisms responsible for muscle tiredness and fatigue observed in patients undergoing chemotherapy, further corroborating the hypothesis that calcium dysfunction could be strictly related to cachectic muscle impairment.…”
Section: Discussionmentioning
confidence: 57%
“…First, as we found an association of CRF with all‐cause mortality in male CRC survivors, special attention should be given to that group, particularly when they have a comorbid heart condition. Second, considering CRF is very prevalent and is associated with survivors’ well‐being and mortality, cancer survivors should be screened for CRF after end of active treatment and survivors suffering from CRF should be advised about fatigue interventions (eg, exercise, pharmacological, psycho‐education, and mind–body therapies) …”
Section: Discussionmentioning
confidence: 99%
“…Cancer‐related fatigue (CRF) is one of the most common and persistent side effects of cancer and its treatment (Ebede, Jang, & Escalante, ; Mohandas, Jaganathan, Mani, Ayyar, & Thevi, ; Wang & Woodruff, ). Fatigue is described as being subjective, multidimensional and variable in severity with physical, emotional, mental, functional and spiritual components (Pearson, Morris, Stefano, & McKinstry, ; Wu & Davis, ). Studies exploring patients' symptom experiences have shown that patients consistently rate fatigue as the most severe symptom, compromising the individual's physical functioning as well as their quality of life (Jung et al, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%